Penggunaan Ceramah dan Leaflet Terhadap Pengetahuan Anak Sekolah Dasar Mengenai Penanganan Pertolongan Pertama Pada Kecelakaan - Brigitta Ayu DS; Qomarudin; Totok Harjanto (Jurnal Keperawatan Notokusumo, 2016)
Background: For elementary school students, knowing the daily handling of first aid is important thing. Using method and media learning which are appropriate for the elementary students can increase the knowledge. Objective: To know the effect of giving lecture and leaflet toward the knowledge level of elementary school students about first aid in Seyegan, Sleman, Yogyakarta. Method: The quasi experimental research with equivalent control group pretest-posttest was done towards 70 students of fifth grade. It consists of 35 students as intervention group and 35 students as control group. Result: The value first aid knowledge average level of intervention group from pretest to posttest increases with p=0.000 (p <0.05). The value first aid knowledge average level of control group from pretest to posttest there was slightly increase with p=0.125 (p> 0.05). Conclusion: Lecture and leaflet are effective to increase the knowledge of fifth grade students of elementary school about first aid in Seyegan, Sleman, Yogyakarta with p=0.000 (p <0.05).